PENGARUH PEMBINAAN MORAL OLEH GURU PENDIDIKAN AGAMA KRISTEN TERHADAP DISIPLIN BELAJAR SISWA KELAS VIII DI SMP NEGERI 3 BALIGE KABUPATEN TOBA SAMOSIR TAHUN PEMBELAJARAN 2018/2019 - hotmaida nadapdap (IAKN Tarutung, 2019)
Abstract, The purpose of this study was to find out how much influence Moral Guidance by Christian ReligiousEducation teachers on the learning discipline of students in SMP Negeri 3 Balige 2018. The method of thisresearch is descriptive and inferential quantitative research methods. The population in this study were allstudents in Balige 3 Public Middle School in 2018 with a total of 102 people with a sample of 51 people.Data was collected by a closed questionnaire of 30 items. The study was conducted on 51 students who were nottrial respondents and validity and reliability were tested. The results of data analysis show that there is apositive and significant effect of Moral Guidance by Christian Religious Education teachers on the learningdiscipline of the of students in 201 Balige Public Middle School.Research data were analyzed with the following steps: 1) Test requirements analysis: a) test positiverelationships obtained rxy = 0.693 = 0.05, n = 51) = 0.297 thus it is known that there is a positiverelationship between variables X with Y variable. B) Test significant relationship obtained value t =6.734rtable ( = 0.05, dk = n-2 = 49) = 2.021 thus there is a significant relationship between variable X andvariable Y. 2) Test of influence: a) Test the regression equation, obtained a regression equation. b) Test theregression coefficient of determination (r2) = 48.06%. 3) Test the hypothesis by using the F test obtainedFcountt table ( Ftable that is 45,347 2,00 thus H0 is rejected and Ha is accepted that is there is a positiveand significant influence Moral Guidance by the Christian Education teacher on the learning discipline of inPublic Middle School 3 Balige 2018.Kata kunci : Pembinaan Moral, Guru PAK, Disiplin Belajar Siswa